2007
DOI: 10.1262/jrd.18036
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Interleukin-18 Receptor mRNA in the Mouse Endometrium

Abstract: Abstract. ) is a proinflammatory cytokine involved in chronic inflammation, autoimmune diseases, and a variety of cancers, and is expressed in mouse uteri. Our previous study suggested that IL-18 acts as a paracrine factor, regulating endometrial function. To elucidate the physiological roles of IL-18 in the mouse endometrium, the expression of the IL-18 receptor (IL-18R) α subunit was analyzed. IL-18Rα mRNA was expressed in several mouse organs in addition to the endometrium. In situ hybridization analysis us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
1
2
2
Order By: Relevance
“…trachomatis [ 39 ]. We observed a 19-fold increase in the expression of Il18r1 in the oviducts of PMSG-treated ESR1KO versus PMSG-treated WT mice (Tables 5 – 8 ), which is also consistent with the regulation of the IL18 receptor by estradiol, as reported in the uterine endometrium [ 40 ]. Among the other DEG’s encoding interleukins, mRNA encoding IL17 receptors A, B and E ( Il17ra , Il17rb and Il17re ) as well as interleukin 1 receptor, type 1 ( Il1r1 ) and interleukin 1 receptor accessory protein ( Il1rap ) differed in the oviducts of PMSG-treated ESR1KO versus PMSG-treated WT mice ( Table 8 ).…”
Section: Discussionsupporting
confidence: 88%
“…trachomatis [ 39 ]. We observed a 19-fold increase in the expression of Il18r1 in the oviducts of PMSG-treated ESR1KO versus PMSG-treated WT mice (Tables 5 – 8 ), which is also consistent with the regulation of the IL18 receptor by estradiol, as reported in the uterine endometrium [ 40 ]. Among the other DEG’s encoding interleukins, mRNA encoding IL17 receptors A, B and E ( Il17ra , Il17rb and Il17re ) as well as interleukin 1 receptor, type 1 ( Il1r1 ) and interleukin 1 receptor accessory protein ( Il1rap ) differed in the oviducts of PMSG-treated ESR1KO versus PMSG-treated WT mice ( Table 8 ).…”
Section: Discussionsupporting
confidence: 88%
“…Medroxyprogesterone prevented inflammation‐induced preterm parturition and significantly preserved fetal viability in pregnant mice treated with LPS 34 . Chronic progesterone significantly decreased IL‐18 receptor mRNA in mouse uteri 35 . Therefore, although in our study the acute effects of progesterone did not influence uterine contraction in pregnant mice with inflammation, a chronic effect of this agent might be a decrease of uterine contractions.…”
Section: Discussioncontrasting
confidence: 53%
“…34 Chronic progesterone significantly decreased IL-18 receptor mRNA in mouse uteri. 35 Therefore, although in our study the acute effects of progesterone did not influence uterine contraction in pregnant mice with inflammation, a chronic effect of this agent might be a decrease of uterine contractions. The administration of progesterone in pregnant mice with alcohol-induced preterm delivery found significant efficacy in prolonging pregnancy.…”
Section: Progesterone Does Not Influence Uterine Contractile Responsecontrasting
confidence: 60%
“…Subsequently, the mRNA expression of IL-18Rα, IL-18Rβ and the soluble form of the IL-18Rβ were detected in the hypothalamus, hippocampus, striatum and cortex and in cultured astrocytes, microglia and neurons [28]. More recently in vivo analysis showed that IL-18Rα mRNA and protein are constitutively expresseed in neurons throughout the brain [26,53,60,66]. Similar neuronal localization and distribution was found for IL-18Rβ (Alboni et al, unpublished data).…”
Section: Introductionmentioning
confidence: 99%